FAKTOR - FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muslimin, 12.05.52.0200; Puspitasari, Elen (Students Journal of Accounting and Banking, 2016)
This research aimed to investigate the factors that influence corporate social responsibility disclosure in the mining company listed on the Indonesia Stock Exchange. The factors that used in this study such as commisioner board, independent commissioner board, managerial ownership, public ownership, company size, profitability, liquidity, leverage, and the companys activities. The population in this study are all mining companies listed on the Indonesia Stock Exchange 2010-2014. There are 38 samples applying purposive sampling technique. Testing the hypothesis in this study using multiple linear regression analysis. The results showed that no significant relationship between managerial ownership, public ownership, company size and liquidity influence the corporate social responsibility disclosure. Meanwhile independent commissioner board, profitability and leverage significant negative influence the corporate social responsibility disclosure. While commisioner board and activities significant positive influence the corporate social responsibility disclosure. Â Keywords:Â Commisioner Board, Independent Commissioner Board, Managerial Ownership, Public Ownership, Company Size, Profitability, Liquidity, Leverage, Activity and Corporate Social Responsibility Disclosure